A systematic review and meta-analysis of disease burden of healthcare-associated infections in China: an economic burden perspective from general hospitals. (May 2022) - Liu, X.; Spencer, A.; Long, Y.; Greenhalgh, C.; Steeg, S.; Verma, A.
Summary: Healthcare-associated infections (HAIs) are a global public health issue. However, the economic burden attributable to HAIs at a national level is unknown in China. The aim of this systematic review was to estimate the direct economic burden caused by HAIs in China. Medline, EMBASE and Chinese Journals Online databases were searched, including studies published from 2009 to 2019. The pooled estimates with 95% confidence interval were calculated with quantile estimation. The random effects model of the DerSimonian–Laird method was used. The statistical significance was set as P <0.05. A total of 2756 publications were identified; six studies were included in a meta-analysis to calculate the pooled estimates of direct economic burden, while five were included in the pooled estimates of the additional economic burden. The pooled median estimates of the total medical expenditure, the medicine expenditure and hospitalization days per inpatient of patients with HAIs were ¥34, 415.62, ¥20, 065.21 and 34.01 days, respectively ( P <0.0001). The pooled median estimates of the differences of the total medical expenditure, the medicine expenditure and hospitalization days per inpatient between patients with HAIs and patients without HAIs were ¥24, 881.37, ¥9, 438.46 and 13.89 days, respectively ( P <0.01). In conclusion, the cost of care for patients with HAIs was significantly higher than that for those without HAIs. This excess economic burden is likely to impact on patients and their families as well as health service providers and the healthcare system as a whole. Effective surveillance systems and cost-effective interventions are needed to control HAIs.